Penicillium oxalicum S-adenosylmethionine synthetase is essential for the viability of fungal cells and the expression of genes encoding cellulolytic enzymes. Issue 1 (January 2021) - Hu, Yueyan; Zhao, Kaili; Qu, Yinbo; Song, Xin; Zhao, Jian; Qin, Yuqi
Abstract: As the universal methyl donor for methylation reactions, S-adenosylmethionine (AdoMet) plays an indispensable role in most cellular metabolic processes. AdoMet is synthesized by AdoMet synthetase. We identified the only one AdoMet synthetase ( Po SasA) in filamentous fungus Penicillium oxalicum . Po SasA was widely distributed in mycelium at different growth stages. The absence of Po SasA was lethal for P . oxalicum . The misregulation of the Po SasA encoding gene affected the synthesis of extracellular cellulolytic enzymes. The expression levels of cellobiohydrolase encoding gene cbh1 / cel7A, β-1-4 endoglucanase eg1 / cel7B, and xylanase encoding gene xyn10A were remarkably downregulated as a result of decreased PosasA gene expression. The production of extracellular cellulases and hemicellulases was also reduced. By contrast, the overexpression of PosasA improved the production of extracellular cellulases and hemicellulases. A total of 133 putative interacting proteins with Po SasA were identified using tandem affinity purification and mass spectrometry. The results of functional enrichment on these proteins showed that they were mainly related to ATP binding, magnesium ion binding, and ATP synthetase activity. Several methyltransferases were also observed among these proteins. These results were consistent with the intrinsic feature of AdoMet synthetase. This work reveals the indispensable role of Po SasA in various biological processes.